2018
DOI: 10.3390/molecules23071671
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Synthesis and Physiological Activities of Flavonoids in Coreopsis lanceolata L. Petals and Their Related Compounds

Abstract: Chalcones, flavanones, and flavonols, including 8-methoxybutin isolated from Coreopsis lanceolata L. petals, were successfully synthesized with total yields of 2–59% from O-methylpyrogallols using the Horner–Wadsworth–Emmons reaction as a key reaction. Aurones, including leptosidin, were also successfully synthesized with 5–36% total yields using the Aldol condensation reaction as a key reaction. Each chalcone, flavanone, flavonol, and aurone with the 3,4-dihydroxy groups in the B-ring showed high antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…From the analysis of HMBC data, unlike compound 3 , this compound was found to have two hydroxy groups attached at positions 7′ and 3′, while the methoxy group at position 4′ was substituted with a hydroxy group. From the comparison with 1 H- and 13 C-NMR data from previous literature, the structure of compound 4 was determined to be 2-(3,4-dihydroxyphenyl)-7-hydroxy-8-methoxy-2,3-dihydrochromen-4-one (8-methoxybutin) [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the analysis of HMBC data, unlike compound 3 , this compound was found to have two hydroxy groups attached at positions 7′ and 3′, while the methoxy group at position 4′ was substituted with a hydroxy group. From the comparison with 1 H- and 13 C-NMR data from previous literature, the structure of compound 4 was determined to be 2-(3,4-dihydroxyphenyl)-7-hydroxy-8-methoxy-2,3-dihydrochromen-4-one (8-methoxybutin) [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…4′,7-Dimethoxyflavanone ( 3 ) is a compound with a flavanone skeleton, reported to have anticancer effects [ 42 ], however there are no reports on its anti-inflammatory activity. 8-Methoxybutine ( 4 ) and leptosidin ( 5 ) are known to have whitening and antioxidant effects and have been reported to be isolated from C. lanceolata [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among chalcones isolated in this study, 3 – 5 showed less inhibitory activity than 2 , indicating that chalcones substituted with additional methoxy group and/or sugar are less effective. The most active compound, 2, has been reported as having various biological, activities such as antileukemic [ 11 ], antioxidant [ 4 ] and anti-cancer [ 5 ], however its DPP-IV potential has not been studied previously. Compounds 6 and 7, with the structures of aurone and flavanone, respectively, exhibited moderate DPP-IV inhibitory effects, while flavone ( 8 ), flavonol ( 9 ) and polyacetylenes ( 1 , 10 and 11 ) did not show their activities.…”
Section: Resultsmentioning
confidence: 99%
“…Coreopsis is a perennial plant belonging to the Compositae family [ 1 ]. It was planted for decoration on the roadsides in North America, Asia and Oceania regions [ 2 , 3 , 4 ]. Typically, C. lanceolata , C. tinctoria and C. drummondii are generally Coreopsis plants distributed all around Korea [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the anti-melanogenic activity of chalcone 21 [13]. To obtain more potent anti-melanogenic agents, we synthesized a series of chalcone derivatives by aldol condensation reactions (Scheme 1) [8,14]. Detailed synthetic procedures and the 1 H-NMR and 13 C-NMR spectroscopic data are shown in the Materials and Methods.…”
Section: Resultsmentioning
confidence: 99%